Byzantine Metal Crosses in Kırklareli Museum - Selda Uygun Yazıcı (Art-Sanat)
The subject of the study is seventeen metal crosses registered in the inventory of Kırklareli Museum. All of the artifacts were brought to the museum through purchasing from Kırklareli and the surrounding districts. Eleven of these artifacts are pendant crosses, and the six of them are reliquary cross. Four of the reliquary crosses are one-sided. Metal crosses, which are unique in Byzantine art, are very rich with examples from different museums, digging areas and collections. The numerous examples obtained from different parts of the empire attest not only to the richness of Byzantine art, but also to the fact that Christianity has always preferred metal crosses as liturgical or personal religious objects. What makes this study different is that there are examples among the crosses of the Kırklareli Museum that are thought to be of Balkan design.